Sources of bias when measuring women’s empowerment in fragile and conflict-affected settings: A story of four case studies - Ambler, Kate; Bloem, Jeffrey R. (International Livestock Research Institute, 2025)
Accurately measuring women’s empowerment systematically across a variety of settings is critical to ensure equal access to market participation, control of the use of productive resources, opportunities for work and decision-making power. Collecting accurate data in fragile and conflict-affected settings, however, is a consistent challenge. For example, the timing of when survey data can be collected safely and differing household composition—due to migration tendencies motivated by safety or economic considerations—can complicate the use of standard survey techniques used to measure women’s empowerment.